Eskimo women and children in front of tents, Teller, ca. 1905 - Nowell, Frank H., 1864-1950 (1905)
Caption on image: Eskimo Women and Mickaninny's Nook, Teller, Alaska. Nowell To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number